The Rise (and Fall) of Tech Clusters - Sergey Kichko; Wen-Jung Liang; Chao-Cheng Mai; Jacques-Francois Thisse; Ping Wang (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Tech clusters play a growing role in knowledge-based economies by accommodating high-tech firms and providing an environment that fosters location-dependent knowledge spillovers and promote R&D investments by .rms. Yet, not much is known about the economic conditions under which such entities may form in equilibrium without government interventions. This paper develops a spatial equilibrium model with a competitive final sector and a monopolistically competitive intermediate sector, which allows us to determine necessary and sufficient conditions for a tech cluster to emerge as an equilibrium outcome. We show that strongly localized knowledge spillovers, skilled labor abundance, and low commuting costs are key drivers for a tech cluster to form. Not only is the productivity of the final sector higher when intermediate firms cluster, but a tech cluster hosts more intermediate firms and more R&D and production activities, and yields greater worker welfare, compared to what a dispersed pattern would generate. With continual improvements in infrastructure and communication technology that lowers coordination costs, tech clusters will eventually be fragmented.
Keywords: D51; L22; O33; R13; 330; high-tech city; knowledge spillovers; intermediate firm clustering; land use; commuting; R&D